Surveying instruments of Greece and Rome - Lewis, M. J. T., 1938- (Cambridge University Press, 2001)
This book contains translations of all the ancient texts on surveying, including major sources hitherto untapped. It sets out to reconstruct the instruments and to explain how they were used. A level of technical sophistication emerges which must count as one of the greatest achievements of the ancient world.